The Effect of Celery Extract on Caspase-3 and TNF-α Gene Expression in Lead Poisoning-Induced Renal Injury in Rats - Purwaningsih, Hesti; Sumarawati, Titiek; Chodidjah, Chodidjah; Putra, Agung; Priyantini, Sri; Fasitasari, Minidian; Ibrahim, Sugeng; Amalina, Nur Dina (International Journal of Cell and Biomedical Science, 2023)
Background To determine the effect of Apium graveolens L (Celery) extract in the TNF-α and caspase-3 gene expression on the lead poisoning-induced renal injury rats’ model. Methods This study is experimental research with post test only control group design. Twenty male Wistar rats were randomly allocated into four groups (n=5). The control group was orally administrated with distillate water. The second group received lead acetate 200mg/kg body weight orally for 14 days, the third group were orally administered lead acetate 200 mg lead acetate/kg body weight and vitamin E 50IU/kg body weight for 14 days. The fourth group was administrated with leas acetate like second group and celery extract 300mg/kg body weight for 14 days. The TNF-a and caspase-3 gene expression was analyses under qRT-PCR. Results The phytochemical analysis of APE indicated the presence of alkaloids, flavonoids, tannins, saponins, and steroids. Leads acetate increased the TNF-α (3.87±0.09) and caspase-3 (7.95±0.23) gene expression. The celery extract was significantly decrease in the TNF-α (3.13±0.34) and caspase-3 (2.48±1.23) gene expression. Conclusion: In conclusion, the presence of celery extract inhibited the renal injury-induced lead acetate toxicity by inhibition of TNF-α proinflammation protein and caspase-3 proapoptosis protein